Convenient Scapegoats: Juvenile Confessions and Exculpatory DNA in Cook County, IL - Cooley, Craig M (2012)
In the Winter of 2011-2012, in two different cases known as the Dixmoor Five and the Englewood Four, nine men were exonerated of rapes and murders based on exculpatory post-conviction DNA testing. Seven of these nine men actually confessed to the crime. This article explores these two cases and how the Cook County law enforcement agencies, including the State's Attorney's Office, dealt with the powerful new DNA results